21 Role of Alpha Crystallin B in Regulation of Differential Mechanism of Myocyte Cell Death During Heart Failure. (19th January 2014) - Mitra, A; Datta, K; Sarkar, S
Abstract : Cardiac hypertrophy and myocardial infarction (MI) are predominant cardiac disease forms with different genetic aetiologies, resulting in severely compromised cardiac function leading to eventual heart failure. Our laboratory has shown that cardiomyocyte apoptosis and ventricular fibrosis are major contributors to heart failure (JCP, 2011; JBC, 2012). Insult to the myocardium transduces multiple signalling pathways that lead towards changes in gene expression regulated by various transcription factors. Our earlier studies threw lights on role of p53 and Nuclear Factor-kappa B (NF-kB) in cardiac diseases and their interactions via a common cofactor p300 that dictates the balancing mechanism of cell death and regeneration during transition of hypertrophy to heart failure. The differential genetic aetiologies between these two disease forms have been addressed by comparative cardiac proteome profiling. Among several altered proteins, the proteomic analysis revealed that mitochondrial outer membrane channel protein VDAC-1 was upregulated exclusively during cardiac hypertrophy, modulating proteins involved in mitochondrial apoptotic pathway whereas, GRP-78, an important upstream regulator of the endoplasmic reticulum (ER) stress pathway, was exclusively upregulated during MI, activating ER stress induced apoptotic pathway. Our study also revealed that small heat shock protein Alpha Crystallin B is instrumental in bypassing the mitochondrial apoptotic pathway during MI via p38 MAPK pathway. Thus, though cardiomyocyte apoptosis is a hallmark for both hypertrophy and MI, the molecular mechanisms involved different sets of proteins and Alpha Crystallin B activated by p38 MAPK plays a crucial role in this process.